STRATEGI KOMUNIKASI POLRESTA PEKANBARU DALAM MENGIMPLEMENTASIKAN PROGRAM JUM’AT BAROKAH - Giovani Dwi Wulandari; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In recent years, public trust toward Indonesian National Police decreases, Kapolri Jendral Tito Karnavian makes a programme Grand Strategy 2016-2025, in implementing the programme, Polresta Pekanbaru makes a social programme named Jum’at Barokah, in this programme, Polresta Pekanbaru wants to show the humanism side from the police officers by helping needful people, dhuafa people, orpans and old people by not considering race, religion, and the background. This programme got so much appreciation from several institutes. The aim of this study is to investigate the communicator strategy, public strategy, message plan, media selection, and the respond toward Polresta Pekanbaru in implementing the programme Jum’at Barokah.This study used Qualitative Research by using descriptive method. The technique research subject selection used purposive technique. The informants for this study were 8 people. The data collecting technique was interview, observation and documentation. The data analysis technique was Interaktif Miles dan Huberman. To achive the data validity of this study, the researcher used the extension of participation and triangulation. Based on the study conducted by the researcher, the findings for the first identification of the problem was communicator strategy in implementing the programme Jumat Barokah Polresta Pekanbaru was Kapolresta Pekanbaru Kombes Pol Susanto S.IK. The target selection strategy was the needful people, dhuafa People, orphans, old people and all Pekanbaru people who were supposed the purpose of this programme. Communication message which was delivered was in informative, persuasive and educative message. The media were printed media, online media, website, and social media. Regarding to the last identification of the problem, the repsond, which was the respond was regarding to the strategy was positive respond from the people.Keyword: Communication Strategy, Jum’at Barokah, Polresta Pekanbaru